2019
DOI: 10.3390/biom9080346
|View full text |Cite
|
Sign up to set email alerts
|

Galangin Activates Nrf2 Signaling and Attenuates Oxidative Damage, Inflammation, and Apoptosis in a Rat Model of Cyclophosphamide-Induced Hepatotoxicity

Abstract: Cyclophosphamide (CP) is a widely used chemotherapeutic agent; however, its clinical application is limited because of its multi-organ toxicity. Galangin (Gal) is a bioactive flavonoid with promising biological activities. This study investigated the hepatoprotective effect of Gal in CP-induced rats. Rats received Gal (15, 30 and 60 mg/kg/day) for 15 days followed by a single dose of CP at day 16. Cyclophosphamide triggered liver injury characterized by elevated serum transaminases, alkaline phosphatase (ALP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
98
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 67 publications
15
98
0
Order By: Relevance
“…Hyperglycemia and hyperlipidemia were associated with increased generation of ROS, oxidative stress, and inflammation [15,86]. The role of ROS in liver injury has been established by studies showing that reduction of ROS can protect against hepatocyte damage induced by several insults [87][88][89]. HFD/STZ diabetic rats in this study showed excessive production of ROS associated with increased MDA and NO.…”
Section: Discussionmentioning
confidence: 52%
“…Hyperglycemia and hyperlipidemia were associated with increased generation of ROS, oxidative stress, and inflammation [15,86]. The role of ROS in liver injury has been established by studies showing that reduction of ROS can protect against hepatocyte damage induced by several insults [87][88][89]. HFD/STZ diabetic rats in this study showed excessive production of ROS associated with increased MDA and NO.…”
Section: Discussionmentioning
confidence: 52%
“…Here, MDA and PCO were significantly increased in the lung of CP-induced rats, demonstrating lipid and protein damage, respectively. In the same context, CP has been recently reported to increase ROS generation and DNA damage in the liver of rats [51].…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, oxidative stress and apoptosis are implicated in CP-induced lung injury. In this context, apoptosis and oxidative injury induced by CP have been reported in different tissues, including lung, liver, and kidney [6,7,[43][44][45][46][50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…The crosstalk between Nrf2 and NF-κB has been reviewed by Wardyn et al [51]. The lack of Nrf2 can aggravate NF-κB activity leading to increased inflammatory cytokine release [52], whereas Nrf2 upregulation resulted in diminished inflammatory responses in rodent models of liver and kidney injury [53][54][55][56][57][58][59][60]. The Nrf2 target gene HO-1 has been demonstrated to inhibit NF-κB-mediated transcription of adhesion molecules possibly through decreasing free intracellular iron in endothelial cells [61].…”
Section: Keap1/nrf2/are Signaling Pathwaymentioning
confidence: 99%